Kualitas Spermatozoa Kauda Epididimis Sapi Bali dengan Penambahan Laktosa atau Maltosa yang Dipreservasi pada Suhu 3–5oC - Labetubun, Jusak; Piter Siwa, Isak (Jurnal Veteriner; Vol 12, No 3 (2011), 2012)
The purpose of this research was to examine the effectivity of lactose or maltose in maintaining theviability of cauda epididymal spermatozoa at Bali cattle when preserved at 3-5 oC. Epididymal spermatozoawere collected by slicing, flashing and pressure of cauda epididymis with normal saline ( 0,9% NaCl). Thecollected spermatozoa were divided in equal volume into three different tubes where each tube was thendiluted with : i) 20 % egg yolk Tris solution (control), ii) 20 % egg yolk Tris solution + 0.6 gram lactose/ 100ml (L 0.6), iii) 20 % egg yolk Tris solution + 0.6 gram maltose/ 100 ml (M 0.6), respectively following this alltubes were kept in a refrigerator at 3-5 oC for six days. The quality of spermatozoa including percentage ofmotility, live, and intact plasma membrane (IPM) were evaluated daily for the six days period. Result atthe study showed that the mean spermatozoa concentration was 11.2 million cells/ml, whilst the mean atpercentage of motility, percentage of live, percentage of abnormality, percentage of cytoplasmic dropletsand percentage of IPM were 75.00%, 86.75%, 10.50%, 14.00% and 86.75%, respectively. At day 7 ofstorage, the percentage of motility, live, and IPM when the spermatozoa were preserved in media containinglactose was 39.00%, 51.40%, and 51.80%, respectively whilst when preserved in media containing maltosewas 38.00%, 49.80% and 52.00%, respectively. The percentage of motility, live and IPM was significantlyhigher (p<0.05) compared to the control. It is therefore concluded that the addition of lactose or maltose inthe preservation media could maintain the quality of the epididymal spermatozoa of Bali cattle.
Keywords: Lactose, maltose, preservation, cauda epididymal spermatozoa, bali bull